Information systems development for decentralized organizations proceedings of the IFIP working conference on information systems development for decentralized organizations, 1995 - Solvberg, Arne (Chapman & Hall, 1995)
TC8 is one of IFIP's most active committees. This book focusses on information systems support for organisations looking particularly at business process reengineering, co-operation between organisations and support for improved work flow in organisations. These are topical subjects and will appeal to both business and research communities.